A Formative Evaluation of Two FASD Prevention Communication Strategies. (10th January 2018) - Driscoll, David L; Barnes, Victoria R; Johnston, Janet M; Windsor, Richard; Ray, Ryan
Abstract : In this FASD prevention feasibility study, we found that FASD prevention messages, particularly paired with pregnancy test dispensers, placed in the women's restrooms of establishments that serve alcohol can effectively promote informed alcohol consumption decisions among women who are, or may become, pregnant. Abstract: Aims: To evaluate the feasibility, acceptability and effectiveness of placing FASD prevention messages in the women's restrooms of establishments serving alcohol in Alaska and the Yukon, regions with high rates of FASD. Methods: Our team placed an FASD educational poster, and posters affixed to a pregnancy test dispenser, in women's restrooms of bars and restaurants. We compared drinking behaviors and knowledge and beliefs about FASD among participants at baseline and at follow-up. Results: Respondents consisted of 2132 women who completed a baseline survey and 1182 women who completed both a baseline and a follow-up survey. Women in both groups showed improvement in knowledge of FASD; the dispenser group scored higher than participants in the poster group on the FASD Health Belief questions at both baseline and follow-up. Forty-three women learned they were pregnant from our pregnancy tests and alcohol consumption among pregnant women was lower at follow-up than at baseline. Conclusions: FASD prevention messages, particularly paired with pregnancy test dispensers, in the women's restrooms of establishments that serve alcohol can effectively promote informed alcohol consumption decisions among women who are, or may become, pregnant. Short Summary: In this FASD prevention feasibility study, we found that FASD prevention messages, particularly paired with pregnancy test dispensers, placed in the women's restrooms of establishments that serve alcohol can effectively promote informed alcohol consumption decisions among women who are, or may become, pregnant.